Effects of postharvest relative humidity and various re-cutting on vase life of cut rose flowers. (16th December 2019) - Chamani, Esmaeil; Wagstaff, Carol
Studies were conducted to evaluate the effects of different relative humidity levels (60%, 75%, and 90%) and re-cutting (0 cm, 1 cm, 2 cm, 3 cm, 4 cm, and 5 cm re-cutting end of flower stem) treatments on vase life of cut rose flower. Two separate experiments (bucket and vase experiments) were conducted based on completely randomised design with factorial arrangement with eight replications in bucket experiment and five replications in vase experiment. Analysis of variance revealed that two ways effect of various RH and re-cuts did not significantly ( P ≤ 0.05) affected flower vase life, relative fresh weight, solution uptake, and bacterial populations. Cut rose flower stored in chamber with 90% relative humidity had the longest vase life, while those one kept in 60% showed the shortest longevity. The result of mean comparisons revealed with increasing relative humidity from 60% to 90%, bacterial populations was increased too.